Kesulitan Guru Kelas III dalam Pembelajaran Tematik di SDN 019 Batang Kulim Kabupaten Pelalawan - Indah Sulistiani; Dea Mustika (IJoIS: Indonesian Journal of Islamic Studies, 2022)
Interesting and meaningful learning for lower grade students is in the form of thematic learning that presents learning themes that are more actual in everyday life. The approach used by the researcher is a descriptive qualitative approach. Sources of data involved 2 teachers and 1 principal with the research instruments used were interview guidelines, observation guidelines, documentation guidelines. This researcher uses 2 data validity techniques, source triangulation and technical triangulation. This data analysis technique uses the Miles and Huberman model, namely data reduction, data presentation, and conclusions. Based on data management, it can be concluded that the difficulties experienced by teachers are found in several indicators such as at the thematic learning planning stage. At the stage of implementing thematic learning, and the thematic learning assessment stage.